基于Pro/E的大传动比减速器虚拟设计 - 李金梁; 宋春华 (Jixie chuandong)
Aiming at the problem which include big volume,heavy weight and trivial design process and so on of large transmission ratio reducer at present,a new kind of reducer by the way of train tandem gear worm transmission and planetary transmission is designed.The reducer has lots of advantages such as the large transmission ratio,small volume and light weight.The parametric 3D modeling of main parts of the reducer are achieved for example the modified gear by Pro/E software,and motion simulation and motion analysis of the reducer are carried out.A new ideas for efficient design of reducer with high transmission ratio is provided by the virtual design.